DESAIN PROFIL GIGI RODA GIGI LURUS DENGAN SISTEM KOORDINAT - Sirod Hantoro; Tiwan Tiwan (Teknoin, 2006)
Design of tooth profile for the big gear enough usually unlike small gear. Process of tooth making is different. The small gear, its tooth making use the machinery process by cutter module, while for the big gear is making to the casting process. One of the method able to be applied in big design gear by using coordinate system. Intention of design of diametrical tooth profile with the coordinate systems is to fulfill the big gear ordering requirement. This method is very benefit to all designer in industry because can be easier in big tooth profile making, so that can fulfill the customer needs. Form the tooth profile for spur gear of coordinate systems with the pressure angle 20 is very good and have sturdy at root tooth. By that is suitable used for big force and low rotationKeywords : Tooth profile, cicloide, evolvente, coordinate systems